Synthesis, characterization, Hirshfeld surface analysis and computational studies of 1-methylpiperazine-1,4-diium bis(hydrogen oxalate): [C5H14N2](HC2O4)2 - Essid, Manel; Muhammad, Shabbir; Marouani, Houda; Saeed, Aqsa; Aloui, Zouhaier; Al-Sehemi, Abdullah G. (Journal of molecular structure, 2020)
A new organic,1-methylpiperazine-1,4-diium bis(hydrogen oxalate) (compound 1) has been synthesized at room temperature. This compound was subject to various characterization studies such as elemental analysis, powder X-ray diffraction, FTIR, UV–Vis and NMR spectroscopy. The structure of the crystal was confirmed by powder X-ray diffraction analysis. The 13C CP-MASNMR spectrum confirms the results predicted by X-ray diffraction. The Hirshfeld surface analysis and fingerprint plot of the compound has been presented to explore the nature of non-covalent interactions and their relative contributions in building the solid-state architecture. Furthermore, the density functional theory (DFT) methods were used to explore the optical and nonlinear optical (NLO) properties of compound 1. The calculated isotropic (αiso) and anisotropic (αaniso) linear polarizabilities are found to be28.42 × 10−24 esu and 4.81 × 10−24 esu, respectively. While the average third-order NLO polarizability <γ>of compound 1 is found to be 40.64 × 10−36 esu at M06/6-31 + G∗ level of theory. A comparison of <γ> amplitude of the studied compound with a prototype NLO molecule of para-Nitroaniline (7.41 × 10−36 esu) showed that <γ> amplitude of compound 1 is ∼5 times larger as compared to that of p-NA. Moreover, the frontier molecular orbitals, molecular electrostatic potential maps are drawn to get several structure-property insights for compound 1. [Display omitted] •The title compound was synthesized at room temperature.•The compound was characterized by powder X-ray diffraction, IR, NMR and UV–visible.•The non-covalent contacts were analyzed by Hirshfeld surface.•The density functional theory (DFT) methods were used to explore the optical and nonlinear optical properties.